Enhancing the environmental sustainability of water treatment sludge (WTS) disposal through blended binder solidification/stabilisation - Nurshamimie, Muhammad Fauzi; Mohd Fadzil, Arshad; Putra Jaya, Ramadhansyah; Mazidah, Mukri; Nor Hanim, Khiyon (EDP Sciences, 2024)
Managing water treatment sludge (WTS) is challenging due to its continuous production and environmental impact. Traditional disposal in landfills is standard but risky for groundwater contamination. Researchers are exploring a more environmentally friendly method using a blend of binders, partially replacing Ordinary Portland Cement (OPC) with waste materials like Waste Paper Sludge Ash (WPSA), Palm Oil Fuel Ash (POFA) and Fly Ash (FA). These materials not only help reduce environmental waste but also decrease cement usage. The study assesses the Atterberg Limits of the treated sludge to design the appropriate solidification/stabilisation (S/S) method, providing essential data on its physical and mechanical properties Using waste materials as binders effectively stabilises the sludge, reducing reliance on cement, cutting disposal costs, and minimizing environmental pollution. The study identifies WPSA as the most suitable replacement, offering self-cementing properties, and demonstrates that combining WPSA OPC, and WTS creates a stable mix with liquefaction resistance. This approach presents a promising, cost-effective, and environmentally solution for WTS management.